Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10549-005-9032-8
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiation therapy (IMRT) reduces the dose to the contralateral breast when compared to conventional tangential fields for primary breast irradiation

Abstract: Primary breast irradiation with tangential IMRT technique significantly reduces the dose to the contralateral breast compared to conventional tangential field techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
4
27
2
1
Order By: Relevance
“…The segment-based techniques offered the possibility of patient-specific intensity modulation in craniocaudal direction improving dose homogeneity with reduced volumes of hot spots, which is in good agreement with previous studies [3,18,23]. The optimization of dose was performed with forward planned segments delivered in step-and-shoot technique [27,36].…”
Section: Discussionsupporting
confidence: 83%
“…The segment-based techniques offered the possibility of patient-specific intensity modulation in craniocaudal direction improving dose homogeneity with reduced volumes of hot spots, which is in good agreement with previous studies [3,18,23]. The optimization of dose was performed with forward planned segments delivered in step-and-shoot technique [27,36].…”
Section: Discussionsupporting
confidence: 83%
“…The average breast dose was similar to the results reported by Jone et al [2] and other measurement points also showed similar results in line with the reported study. The dose near the treatment site was found to be higher than the data reported by Ajay et al [14]. However, this could be due to the possible measurement at the inner point of measurement.…”
Section: Discussioncontrasting
confidence: 65%
“…To date, several investigations of the use of the FIF technique to improve dose distribution have been reported [20,[26][27][28][29][30][31][32][33]. FIF techniques are able to decrease the scattered doses to the contralateral breast and other parts of the body compared with conventional tangential field techniques [34,35], because of the use of MLCs instead of PWs. In our study, the FIF-RT technique for WBRT significantly reduced the volumes receiving doses over the prescription dose in irradiated volumes and improved the dose homogeneity of PTV eval compared with the TanPW-RT technique.…”
Section: Discussionmentioning
confidence: 99%